2012
DOI: 10.1111/j.1469-0691.2011.03606.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of multidrug resistance in healthcare-associated and nosocomial Gram-negative bacteraemia on mortality and length of stay: cohort study

Abstract: Multidrug-resistant Gram-negative bacteria (MDR-GNB) are an emerging public health threat. Accurate estimates of their clinical impact are vital for justifying interventions directed towards preventing or managing infections caused by these pathogens. A retrospective observational cohort study was conducted between 1 January 2007 and 31 July 2009, involving subjects with healthcare-associated and nosocomial Gram-negative bacteraemia at two large Singaporean hospitals. Outcomes studied were mortality and length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
84
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 27 publications
10
84
3
1
Order By: Relevance
“…The MDR phenotype was not associated with either in-hospital mortality or poor clinical outcome. This is consistent with the literature, as multiple large studies have demonstrated antibiotic resistance to have either a detrimental or neutral effect on clinical outcomes (37)(38)(39)(40). In this study, the assessment of how antibiotic resistance influences clinical outcomes is likely complicated by heterogeneity in bacterial species, antibiotic resistance profiles, and patient clinical factors.…”
Section: Discussionsupporting
confidence: 85%
“…The MDR phenotype was not associated with either in-hospital mortality or poor clinical outcome. This is consistent with the literature, as multiple large studies have demonstrated antibiotic resistance to have either a detrimental or neutral effect on clinical outcomes (37)(38)(39)(40). In this study, the assessment of how antibiotic resistance influences clinical outcomes is likely complicated by heterogeneity in bacterial species, antibiotic resistance profiles, and patient clinical factors.…”
Section: Discussionsupporting
confidence: 85%
“…Prevention and management of infection is imperative as postoperative SSI alone can prolong hospitalization, double readmission rates, and triple the cost of treatment [5]. Inappropriate use of antibiotics, however, can increase resistance towards antibiotics, morbidity, mortality and cost of health-care [6,7,8,9]. This study determined the appropriateness of antibiotic prescription among surgical patients and will act as an important guide in the development and implementation of an effective ASP.…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true in the hospital environment (intensive care units, burn units, etc. ), in which if a opportunistic pathogen is drug resistant, it can cause disease more readily (12). In environments where selective antibiotic pressure prevails, some opportunistic pathogens are able to colonize new ecological niches because of their plasticity and ability to adapt through the acquisition or development of mechanisms of resistance and persistence.…”
mentioning
confidence: 99%